VD_FINDINFO HC / 2025 / 54 vom 19. Mai 2025 - VD Tribunal cantonal (2025)
OBLIGATION D'ENTRETIEN, PROTECTION DE L'UNION CONJUGALE, REVENU HYPOTHÉTIQUE, MOTIVATION DE LA DEMANDE | 163 CC, 176 al. 1 ch. 1 CC, 276 CC, 285 CC